Food nutrition and toxicology targeting on specific organs in the era of single-cell sequencing - Xiaofei Wang; Xiaowen Cheng; Huiling Liu; Xiaohuan Mu; Hao Zheng (Food Science and Human Wellness)
Due to the complex natures of dietary food components, it is difficult to elucidate how the compounds affect host health. Dietary food often selectively presents its mechanism of action on different cell types, and participates in the modulation of targeted cells and their microenvironments within organs. However, the limitations of traditional in vitro assays or in vivo animal experiments cannot comprehensively examine cellular heterogeneity and the tissue-biased influences. Single-cell RNA sequencing (scRNA-seq) has emerged as an indispensable methodology to decompose tissues into different cell types for the demonstration of transcriptional profiles of individual cells. ScRNA-seq applications has been summarized on three typical organs (brain, liver, kidney), and two representative immune- and tumor related health problems. The ever-increasing role of scRNA-seq in dietary food research with further improvement can provide sub-cellular information and the coupling between other cellular modalities. In this review, we propose utilizing scRNA-seq to more effectively capture the subtle and complex effects of food chemicals, and how they may lead to health problems at single-cell resolution. This novel technique will be valuable to elucidate the underlying mechanism of both the health benefits of food nutrients and the detrimental consequences food toxicants at the cellular level.